Ultra-low friction W–S–N solid lubricant coating - Gustavsson, Fredrik (2013)
W–S–N films were deposited by reactive magnetron sputtering from WS2 target in Ar/N2 atmosphere. Besides the standard evaluation of composition, structure, morphology, hardness and cohesion/adhesion, the core objective of this paper was to analyze coating tribological behavior. The chemical composition was 34 at.% N, 12 at.% O, 29 at.% W and 25 at.% S, and the as-deposited films were completely amorphous. The film thickness was 2.3 μm, including the approximately 300-nm thick adhesion improving titanium interlayer. The friction coefficient was lower than 0.003 when sliding in dry nitrogen. The coating showed remarkable wear resistance surviving more than 2 million laps on pin-on-dics. The excellent friction properties were attributed to the formation of a thin tungsten disulfide tribofilm on the top of the wear track of the coating and on the counterpart surface. Moreover, the coating showed ability to replenish damaged areas with solid lubricant. We demonstrated that a structural transformation of the coating from an amorphous-like to a gradient quasi-ordered structure and an ordered transfer layer formation improved mechanical properties and radically decreased friction and wear.